(3cTa GdCSQGQ hgJc GdCSJGQs - (3LeGd GdOjf Hf gdGd GdUaOj,J (B696 (3g` s
(3ChdgG (B:s
(3JaSjQ bhdg JYGdi (B:"(3Ef JcaQhG aEf Gddg Zfj Yfce , hdGjQVi dYHGOI GdcaQ(B" (3ef ShQI GdReQ s
(3BNQgG (B:s
(3BNQ GdbQBf s
(3GdfSNI HgG MhGTs
(3ebOGQ GdfbU HGdeNWhW(B: (3ef Chd (B"(3GdReQ(B" (3Edi GdCjI GdeHJOCI HgG GdeLdOIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B256s
Keywords: (3GdJaSjQ hYdhe GdbQBfs